2001
DOI: 10.1536/jhj.42.701
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Propafenone on Premature Ventricular Contractions (PVC). An Analysis Based on Heart Rate Dependency of PVCs.

Abstract: SUMMARYThe effect of 450 mg/day propafenone for two weeks on premature ventricular contractions (PVCs) was studied in combination with an assessment of heart rate (HR) dependency of PVCs using Holter ECG monitoring in patients with more than 720 PVCs per day. The PVC-HR correlation was classified into positive (P), bidirectional (B), and flat and negative (FN) correlation groups. The positive group included only patients in whom PVC frequency increased with a heart rate increase, while the bidirectional group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Another study suggested that beta-blockers were most effective in reducing PVC frequency in the tachycardia and indifferent groups (Pitzalis et al, 1996). Propafenone has also been shown to be most effective in tachycardia-enhanced patients (Saikawa et al, 2001). …”
Section: Pvcs and Heart Ratementioning
confidence: 99%
“…Another study suggested that beta-blockers were most effective in reducing PVC frequency in the tachycardia and indifferent groups (Pitzalis et al, 1996). Propafenone has also been shown to be most effective in tachycardia-enhanced patients (Saikawa et al, 2001). …”
Section: Pvcs and Heart Ratementioning
confidence: 99%
“…Sodium channel blockers have a class I (level of evidence C) recommendation in symptomatic patients with VA in the absence of underlying structural heart disease [15]. Class Ic antiarrhythmic drugs (AAD; e.g., propafenone and flecainide) are very effective, with up to 80% VA burden reduction in 50–74% of patients, and they are relatively well tolerated by the patient [6, 16, 17]. However, these agents have led to increased mortality in patients with structural heart disease and, hitherto, a thorough analysis in structurally normal hearts is lacking; therefore, caution is advised.…”
Section: Introductionmentioning
confidence: 99%